Surveillance Report on Endemic Measles in District Bannu (Medical Forum Monthly, 2024)
Objective: The objective of the current study was to report the surveillance of endemic measles in district Bannu and its peripheries.Study Design: Observational / descriptive study,Place and Duration of Study: The study was conducted in Women and Children Teaching Hospital Bannu and various BHUs and dispensaries of countryside’s of the district from Jan, 2016 to March, 2016.Materials and Methods: Patients up to 16 years old were screened for febrile rash illnesses at women and children teaching hospital district Bannu and BHUs/dispensaries. Active measles cases were classified as measles, measles with eye and mouth complications, or severe complicated measles using IMCI criteria.16 most critical patient’s blood samples were sent to CMH hospital laboratory Peshawar, KPK for further confirmation where test was done by ELISA technique utilizing IgM antibodies.Results: Results showed that male children were highly infected than female. Children from 1-3 years were most affected, followed by children with 1 to 12 months. Least no of cases were reported in children from 4-8 years. Bannu city surrounded areas like mammashkhel, shiekhan, surrani were more affected from measles outbreak while nearby areas are at constant threat.Conclusion: It is concluded that the peripheries were more affected from measles outbreak while nearby areas are at constant threat. In light of our findings, it can be stated that proper steps should be taken by government and non-government organization to control the situation in affected areas and to prevent the nearby areas specially the city from the current outbreak.